Analysis Engine Performance PT6A-114A after Applying TBO Extension with the Manufacture Limitation - Rahmawati, Fajar Khanif (Institut Teknologi Dirgantara Adisutjipto, 2018)
Engine PT6A-114A is used on Cessna Grand Caravan 208B which has basic TBO : 3.600FH. Through condition monitoring, manufacturers issued SB1703R9 regarding allowing extension TBOs with terms and conditions. The analysis is done by comparing the condition of the TBO engine : 3.600FH and the engine that has been extended to TBO : 5.600FH. From the data obtained by engine with TBO : 3.600FH and TBO : 5.600FH on the cruising phase, the ITT achieved at each altitude does not exceed the maximum limitation which is 740oC. . Whereas through analytic calculations, the parameters of engine performances are: fuel / air ratio, thrust specifications, specific fuel consumption, thermal efficiency, propulsive efficiency, overall efficiency, and specific power, match to the ideal conditions when compared to altitude. It can be concluded that parameters engine with TBO: 3.600FH or TBO : 5.600FH are still within the limits and engine parameters confirmed to ideal conditions.